(3GdehLR aj GdWHs - (3YdGA GdOjf Ydj GHf GHi GdMRe GdbQTi ,GHf GdfajSs; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdYdGeI gPG GdcJGH Ydi CQHYI afhf Gdaf GdChd ai bhGYO Gdaf GdKGfi ai GdCOhjI s
(3BNQgG (B:s
(3hbO YV cdH cdH CQHYjf QLdG aCcd HYVge ef cHOg hGSJfca GdHGbi Yf CcdgG ,aef Ccd efgG de jeJ Je GdcJGH s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B264 s
Keywords: (3GdWHs